Comparable cellular and humoral immunity upon homologous and heterologous COVID-19 vaccination regimens in kidney transplant recipients - Körber, Nina; Holzmann-Littig, Christopher; Wilkens, Gesa; Liao, Bo-Hung; Werz, Maia L.; Platen, Louise; Cheng, Cho-Chin; Tellenbach, Myriam; Kappler, Verena; Lehner, Viktor; Mijočević, Hrvoje; Christa, Catharina; et al. (Frontiers in Immunology, 2023)
Background Kidney transplant recipients (KTRs) are at high risk for a severe course of coronavirus disease 2019 (COVID-19); thus, effective vaccination is critical. However, the achievement of protective immunogenicity is hampered by immunosuppressive therapies. We assessed cellular and humoral immunity and breakthrough infection rates in KTRs vaccinated with homologous and heterologous COVID-19 vaccination regimens. Method We performed a comparative in-depth analysis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific T-cell responses using multiplex Fluorospot assays and SARS-CoV-2-specific neutralizing antibodies (NAbs) between three-times homologously (n = 18) and heterologously (n = 8) vaccinated KTRs. Results We detected SARS-CoV-2-reactive T cells in 100% of KTRs upon third vaccination, with comparable frequencies, T-cell expression profiles, and relative interferon γ and interleukin 2 production per single cell between homologously and heterologously vaccinated KTRs. SARS-CoV-2-specific NAb positivity rates were significantly higher in heterologously (87.5%) compared to homologously vaccinated (50.0%) KTRs (P < 0.0001), whereas the magnitudes of NAb titers were comparable between both subcohorts after third vaccination. SARS-CoV-2 breakthrough infections occurred in equal numbers in homologously (38.9%) and heterologously (37.5%) vaccinated KTRs with mild-to-moderate courses of COVID-19. Conclusion Our data support a more comprehensive assessment of not only humoral but also cellular SARS-CoV-2-specific immunity in KTRs to provide an in-depth understanding about the COVID-19 vaccine–induced immune response in a transplant setting.